Buzzing Hemisphere / Rumor Hemisférico - Noel, Urayoán (Book collections on Project MUSE., 2015)
"Buzzing Hemisphere / Rumor Hemisferico imagines an alternative to the monolingualism of the U.S. literary and political landscape, and proposes a geo-neuro-political performance attuned to marginalized forms of knowledge, perception, and identity. Poet Urayoán Noel maps the spaces between and across languages, cities, and bodies, creating a hemispheric poetics that is broadly geopolitical and intimately neurological"--Provided by publisher.